PENGARUH GAYA HIDUP, WORD OF MOUTH, DAN KUALITAS LAYANAN TERHADAP KEPUTUSAN PEMBELIAN PADA PEGIPEGI - Alya Aulinawan (2020)
This research is a quantitative study that aims to determine the effect of lifestyle, word of mouth, and service quality on purchasing decisions. The population in this study are consumers who knowand use the services of PegiPegi in Tebet sub - distric, South Jakarta. The size of the sample taken 75 respondents with probability sampling techniques and simple random sampling method. Data collection is done through the distribution of questionnaires with the analysis technique used is the partial least square (PLS) analysis method with SmartPLS 3.0 software. The results of this study indcate that (1) lifestyle doesn't have a positive and significant effect on purchasing decisions with a coefficient value of 0,289 (2) word of mouth has a positive and not significant effect on purchasing decisions with a coefficient value of 0,082 (3) quality of service has a positive and significant to the purchase decisions eith a coefficient of 0,537.